Training in clinical psychological intervention at the university: an experience of research-intervention for a Mental Health Service - Virginia Aloi, Caterina; Avilloni, Kristian; Biagioli, Serafina; Capozzi, Veronica; Fiorentino, Risia; Leone, Nicola; Pretto, Raffaela; Ruggiero, Luca; Russo, Elena; Violi, Eliana (Quaderni di Psicologia Clinica, 2014)
This paper deals with a research-intervention experience, regarding Mental Health Services (MHSs). It was proposed by a chair of the Department 42 of Sapienza University to a Mental Health Department in Rome, in particular to one of its Mental Health Centers. The research-intervention involved a group of roman citizens as direct or indirect customers of MHSs. The results of the research-intervention, based on analysis of the demand method, are properly discussed in another paper previously published (Paniccia, Dolcetti, Giovagnoli, & Sesto, 2014). This contribution specifically aims to analyze training experience in research-intervention from students’ perspective who took part in the research group. An interpretation of this experience is suggested through three categories that organize the relationships between the Mental Health Center and the training context, with the emotional dynamics connected to them: familism, individualism, extraneousness.